2010
DOI: 10.3109/00498250903509375
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of HIV protease inhibitors with OATP1B1, 1B3, and 2B1

Abstract: The effects of human immunodeficiency virus (HIV) protease inhibitors (PI) on the accumulation of the fluorescent bile salt analogue cholyl-glycylamido-fluorescein (CGamF) were determined in organic anion transporting polypeptide (OATP)-1B1 and -1B3-expressing Chinese hamster ovary (CHO) cells. In addition, interaction studies in Caco-2 monolayers, known only to express the OATP2B1 isoform, were conducted using the established OATP substrate estrone 3-sulfate (E3S), since no CGamF accumulation was observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
117
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(129 citation statements)
references
References 51 publications
10
117
1
1
Order By: Relevance
“…As shown in Fig. 4B, in both nontransduced (None) and Ad-OATP1B3-transduced human SCH (Ad-OATP1B3), PKC activation by PMA treatment (0.1 mM, 30 minutes) significantly inhibited [ 3 H]CCK-8 accumulation to an extent close to the inhibition by 100 mM BSP, a potent inhibitor of OATPs (Annaert et al, 2010).…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…As shown in Fig. 4B, in both nontransduced (None) and Ad-OATP1B3-transduced human SCH (Ad-OATP1B3), PKC activation by PMA treatment (0.1 mM, 30 minutes) significantly inhibited [ 3 H]CCK-8 accumulation to an extent close to the inhibition by 100 mM BSP, a potent inhibitor of OATPs (Annaert et al, 2010).…”
Section: Methodsmentioning
confidence: 90%
“…Recently, OATP1B1 and OATP1B3 have been recognized as important determinants of transport-mediated drug-drug interactions (DDIs) (Tweedie et al, 2013). Many drugs that are potent OATP inhibitors in vitro [e.g., cyclosporine (Letschert et al, 2006) and ritonavir (Annaert et al, 2010)] may cause clinically significant DDIs in vivo; for example, significant increases in the systemic exposure of statins have been reported when these OATP inhibitors are coadministered with statins, which are OATP substrates (Shitara et al, 2003;Kiser et al, 2008). OATP1B3 shares a variety of common substrates with OATP1B1, such as statins (Hirano et al, 2004;Kitamura et al, 2008), rifampicin (Vavricka et al, 2002), and bromosulfophthalein (BSP) (Cui et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…[178,179] Thus, the inhibition of the enterocytic influx via OSTa/b is probably not of concern with regards to DDIs. However, OSTa/b is also an intestinal basolateral absorptive transporter (along [165,168] 4.0/4.6 a Simvastatin [164] 85 a Tipranavir [165] 0.9 a OATP3A1_v1 (OATP-D)…”
Section: Oatp1a2 (Oatp-a)mentioning
confidence: 99%
“…Atorvastatin [164] 0.2 Atazanavir [165] 3.6 a Estriol [158] Benzylpenicillin [35] Atorvastatin [164] 0.7 Pregnenolone sulfate [158] Estrone [158] Bosentan [166] 202 Benzylpenicillin [36] 16 000 a Prostaglandin E2 [35] Pregnenolone sulfate [157,158] 3.5 a Fexofenadine [41] Cerivastatin [164] 66 a Taurocholate [41] 72 Testosterone [158] 15 a /21 a Fluvastatin [162,167] 0.7 Cimetidine [36] Glibenclamide [163] 6.3 Ciclosporin [154] 0.07 a Pitavastatin [161] 1.2 Darunavir [165] 26 a Pravastatin [37,41] 2250 Digoxin [164] Rosuvastatin [87,154] 2.4/6.4 Efavirenz [165] 9.6 a Tebipenem pivoxil [156] >1000 Gemfibrozil [154,162,164] 8 a Glibenclamide [164] Indinavir [168] 3.0 Indometacin [36,164] Lopinavir [165] 0.7 a Lovastatin [164] Memantine [164] Mifepristone [158] 2.2 a /4.7 a Nelfinavir [165] 0.9 a Pravastatin [36,37] 5 500 a /1 020 a Probenecid …”
Section: Oatp1a2 (Oatp-a)mentioning
confidence: 99%
“…12,13 Several studies have illustrated that HIV PI inhibit the in vitro cellular uptake of OATP1B probe substrates like estradiol-17β-D-glucuronide, CGamF and sodium fluorescein. [14][15][16][17] Moreover, it has been suggested that inhibition of these membrane transporters contributes to clinically important antiretroviral drug-drug interactions, for example with cerivastatin and atorvastatin. 18 While these examples certainly illustrate the clinical relevance of OATP modulation by HIV PI, the concept of meaningful OATPmediated transport of HIV PI remains controversial.…”
Section: Introductionmentioning
confidence: 99%